Making an urban environmental climate map of the Bangkok Metropolitan Region, Thailand: Analysis of air temperature, wind distributions, and spatial environmental factors - Tarnrawee Ngamsiriudom; Takahiro Tanaka (World Development Sustainability, 2023)
Urban heat islands (UHIs) are a global phenomenon. They are particularly evident in expansive urban centers such as Bangkok, Thailand's capital. Recent research has highlighted the escalation of temperatures and poor ventilation due to severe urbanization. Nevertheless, scant attention has been paid to both temperature and wind distribution. Concurrently, the imperatives of urban development policies require the integration of environmental and climatic factors. In this context, the present study delves into the UHIs in Bangkok and the climatic dynamics within the expansive Bangkok Metropolitan Region (BMR), encompassing six provinces. Utilizing climate data from 68 observation stations in 2019, this study aims to unravel the intricate interplay between air temperature distributions, wind distributions, and spatial environmental factors within the BMR, with the ultimate objective of constructing a comprehensive Urban Environmental Climate Map (UECM) tailored to the BMR. This study comprises three key stages. Initially, the authors classified the spatial-physical attributes of observation points, encompassing variables such as land use and land coverage (LULC). Subsequently, an exhaustive analysis was conducted to delve into the relationship between the climate distributions and spatial environmental factors. The insights lead to a refined UECM that encapsulates the BMR's climatic intricacy. The results of this study yield novel findings. Nocturnal air temperature fluctuations within the BMR exhibited a discernible correlation with green cover and proximity to water resources. Conversely, diurnal temperature variations predominantly hinge on the distance from the coastline in the direction of the sea breeze (DCDS). Moreover, during summer, the diurnal wind speed demonstrated a significant correlation with DCDS and the building coverage. Therefore, the UECM for the BMR was divided into nine distinct zones, each associated with varying degrees of recommendations for LULC and ventilation enhancement. Notably, the priority zones for heat mitigation efforts are mostly located in the central Bangkok. This study has academic implications. It has the capacity to inform and shape governmental policies and urban planning across BMR provinces. Stakeholders aim to gain a better understanding of their environmental milieu. These findings advocate future urban planning by integrating UECMs and design guidelines that consider science and policy. This approach is suitable for sustainable urban development.